A Review of Programs That Targeted Environmental Determinants of Aboriginal and Torres Strait Islander Health - Kevin Rowley (International Journal of Environmental Research and Public Health, 2013)
Objective: Effective interventions to improve population and individual health require environmental change as well as strategies that target individual behaviours and clinical factors. This is the basis of implementing an ecological approach to health programs and health promotion. For Aboriginal People and Torres Strait Islanders, colonisation has made the physical and social environment particularly detrimental for health. Methods and Results: We conducted a literature review to identify Aboriginal health interventions that targeted environmental determinants of health, identifying 21 different health programs. Program activities that targeted environmental determinants of health included: Caring for Country; changes to food supply and/or policy; infrastructure for physical activity; housing construction and maintenance; anti-smoking policies; increased workforce capacity; continuous quality improvement of clinical systems; petrol substitution; and income management. Targets were categorised according to Miller’s Living Systems Theory. Researchers using an Indigenous community based perspective more often identified interpersonal and community-level targets than were identified using a Western academic perspective. Conclusions: Although there are relatively few papers describing interventions that target environmental determinants of health, many of these addressed such determinants at multiple levels, consistent to some degree with an ecological approach. Interpretation of program targets sometimes differed between academic and community-based perspectives, and was limited by the type of data reported in the journal articles, highlighting the need for local Indigenous knowledge for accurate program evaluation. Implications: While an ecological approach to Indigenous health is increasingly evident in the health research literature, the design and evaluation of such programs requires a wide breadth of expertise, including local Indigenous knowledge.